2015
DOI: 10.1017/s204579601500027x
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of common mental disorders from age 20 to 50: results from the prospective Zurich cohort Study

Abstract: Background:There are only a small number of prospective studies that have systematically evaluated standardised diagnostic criteria for mental disorder for more than a decade. The aim of this study is to present the approximated overall and sex-specific cumulative incidence of mental disorder in the Zurich cohort study, a prospective cohort study of 18–19 years olds from the canton of Zurich, Switzerland, who were followed through age 50.Method:A stratified sample of 591 participants were interviewed with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
59
2
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 31 publications
5
59
2
6
Order By: Relevance
“…Estimates from large-scale, cross-sectional population surveys that were initially criticized for being too high [1][2][3][4][5][6] have been replicated 7,8 and followed by even higher estimates of cumulative risk from prospective studies [9][10][11][12][13] that repeatedly assessed mental health disorder over time. For example, prospectively generated prevalence estimates in the Baltimore site of the Epidemiologic Catchment Area (ECA) study were 2 to 12 times higher than those estimated retrospectively, corroborating the idea that retrospective assessment may underestimate mental health disorder frequency owing to reliance on recall.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates from large-scale, cross-sectional population surveys that were initially criticized for being too high [1][2][3][4][5][6] have been replicated 7,8 and followed by even higher estimates of cumulative risk from prospective studies [9][10][11][12][13] that repeatedly assessed mental health disorder over time. For example, prospectively generated prevalence estimates in the Baltimore site of the Epidemiologic Catchment Area (ECA) study were 2 to 12 times higher than those estimated retrospectively, corroborating the idea that retrospective assessment may underestimate mental health disorder frequency owing to reliance on recall.…”
mentioning
confidence: 99%
“…Although a number of studies, such as that of Colman et al, 16 have estimated trajectories of symptoms over time, descriptions of trajectories of mental health disorder are scarce. The few diagnostic studies 9,[17][18][19][20] that have followed population-based samples of adults for more than 20 years have provided important information about the incidence and course of specific disorders. Along with longitudinal studies 19,21-29 of children followed into early adulthood, these indicate a substantial degree of heterogeneity in course and comorbidity with other mental health disorders over time.…”
mentioning
confidence: 99%
“…7 Disorders caused by the use of drugs, regardless of their type, presented a cumulative incidence of 16.78% (95% CI 15.18-18.54), being 20.50% among men and 13.39% among women in South Africa. 14 In pregnant women, the use of marijuana was associated with a higher probability for the development of depression. 8 Regarding age, this study showed that age ≤25 years was associated with a higher probability of developing CMD in the population studied.…”
Section: Discussionmentioning
confidence: 99%
“…Summers & Barber, 2010). Recent studies have shown that the approximated cumulative incidence of depression diagnosis from childhood to adulthood is between 32.54 and 51% (Rohde et al 2012;Angst et al 2015).…”
Section: What Do We Know About the Efficacy Of Psychotherapies For Dementioning
confidence: 99%
“…Summers & Barber, 2010). Recent studies have shown that the approximated cumulative incidence of depression diagnosis from childhood to adulthood is between 32.54 and 51% (Rohde et al 2012;Angst et al 2015).In the past several decades, over 400 randomised clinical trials have investigated the efficacy of psychotherapy for depression (Cuijpers, 2015). Despite the heated debate regarding the superiority of one treatment over others, there is fairly wide acceptance of the 'Dodo Bird Verdict ' (Luborsky et al 1975), at least in the case of depression, suggesting that all treatments are more or less equally effective (Cuijpers et al 2008;Barth et al 2013).…”
mentioning
confidence: 99%